Determinants of teacher professional development for medical universities towards sustainability / Lu Liu ... [et al.] - Lu, Liu; Voon, Boo Ho; Hamzah, Muhammad Iskandar; Jiajie, He (Universiti Teknologi MARA, 2025)
By exploring the relationship between organizational support and teachers' professional development, this study searched for the determinants of teachers' professional development towards sustainability in Chinese medical universities. Despite advances in the relevant literature, there is still a lack of empirical research examining the promotion of teacher professional development within the same model. After going through the literature review, the research model and research hypotheses were formulated. A quantitative investigation was also conducted and the hypothesized relationships were tested using structural equation modelling on 606 data samples. It was found that organizational support directly and significantly affects teachers' self-efficacy, professional identity and professional ideals; the findings further suggest that self-efficacy and professional ideals mediate the relationship between organizational support and teacher professional development. Whereas the direct relationship between organizational support and teacher professional development was not significant, professional identity did not play a mediating effect between them. The findings from the study guide managers to be more effective in carrying out organizational behaviors that promote teacher professional development. The study further improved managers' understanding of the relationship between organizational support and teacher professional development. Although there has been some previous causal research discussing how to promote teacher professional development. However, there have been few studies focusing on empirical studies combining individual differences, environment, and behavioral outcomes, and there is a gap, especially in the local medical university faculty population.